The Effect of Credit Risk and Bank Size on Bank Profitability in Indonesia Before and During the Covid-19 Pandemic - Muhamad Wajahid; Ferryal Abadi (Universitas KH. Abdul Chalim Mojokerto, 2024)
Competency is a person's characteristic that can directly impact a person's performance in carrying out work or tasks on the basis of skills, knowledge and attitudes that show the employee's professionalism so that they have a competitive advantage in a particular job, with skilled behavior, competitive work and a good attitude. This research aims to further explore the influence of competency and work discipline on employee performance through motivation of company employees operating in the forward manufacturing sector located in jakarta. In this research, 137 respondents were obtained who were employees of companies operating in the forward manufacturing sector by distributing online questionnaires. Respondents for this research were selected using a purposive sampling method. This research is quantitative research using the Structural Equation Model (SEM) method, while data analysis and processing uses SMART-PLS software. The research results show that competency has an influence on work motivation, work discipline has a positive influence on motivation, motivation has a positive influence on employee performance, competency has no influence on employee performance and work discipline has an influence on employee performance. The managerial implication of the research for organizations is to contribute to improving employee performance by providing motivation and applying discipline in order to improve their ability to work.